Applying a physiotherapy protocol to women during the active phase of labor improves obstetrical outcomes: a randomized clinical trialAJOG Global Reports at a Glance - Licia Santos Santana, XX; Rubneide Barreto Silva Gallo, XX; Silvana Maria Quintana, XX; Geraldo Duarte, XX; Cristine Homsi Jorge, XX; Alessandra Cristina Marcolin, XX (Elsevier, 2022)
BACKGROUND: Labor is a physiological process triggered by mechanical and hormonal events that promote uterine contractions to expel the fetus. OBJECTIVE: This study aimed to evaluate the effectiveness of a nonpharmacologic childbirth care protocol in women in the active phase of labor in improving obstetrical and perinatal outcomes. STUDY DESIGN: This was a randomized trial with concealed allocation, assessor blinding, and intention-to-treat analysis. A total of 80 low-risk primigravida women at the end of pregnancy admitted at the beginning of the active phase of labor participated in the study. The participants were divided into an experimental group (n=40) and a control group (n=40). Women in the experimental group received 4 interventions: ambulation at 4 to 6 cm of cervical dilation, alternation of maternal postures, transcutaneous electrical nerve stimulation at 6 to 7 cm, and a warm shower bath at >7 cm. The control group received only routine obstetrical care during labor. The parturient could request pharmacologic analgesia at any time during the study. The main outcome measures were the duration of the active phase of the first stage of labor, the duration of the expulsive phase of labor, and the prevalence of labor dystocia as assessed by the partograph. The researchers collected other maternal and neonatal data from official birth records. RESULTS: The parturients who received the nonpharmacologic protocol had a shorter active phase of the first stage of labor (444 minutes in the control group and 373 minutes in the experimental group; P=.02), presented rupture of membranes later in labor (7 cm in the control group and 8 cm in the experimental group; P<.01), requested pharmacologic analgesia with more significant cervical dilation (5 cm in the control group and 8 cm in the experimental group; P<.01), requested fewer additional doses of analgesics, and had lower labor dystocia rates than the patients in the control group. In addition, there was no difference in other maternal and perinatal variables between the control group and the experimental group. CONCLUSION: The implementation of a sequential nonpharmacologic protocol composed of ambulation, transcutaneous electrical nerve stimulation with change of upright positions, and warm shower bath has the potential to reduce labor pain, as reflected in decreased and delayed use of pharmacologic analgesia and reduced duration of the active phase of labor and dystocia rates. Maternity hospitals should provide this protocol, and women should be encouraged to request this childbirth care protocol.